# Database - The Relational Model and Normalization - Discussion

Discussion Forum : The Relational Model and Normalization - General Questions (Q.No. 19)
19.
If attribute A determines both attributes B and C, then it is also true that:
A → B.
B → A.
C → A.
(B,C) → A.
Explanation:
No answer description is available. Let's discuss.
Discussion:
22 comments Page 1 of 3.

Rohit bhatia said:   6 years ago
@ALL.

Every time attribute A appears, it is matched with the same value of attribute B, but not the same value of attribute C. Therefore, it is true that:

A. A -> B.
B. A -> C.
C. A -> (B,C).
D. (B,C) -> A.

So, How it's answer is same as above question? Please, anyone explain me.

Abhijit said:   7 years ago
Thanks @Kamlesh.

Sreepada B l said:   7 years ago
Please explain, how option A is true.

Rahul said:   7 years ago
Give brief explanation for option A.

Prachi said:   7 years ago
There is a different between determines and determine of.

If determine of then B->A but here determines B and C so A->B.

Karan said:   8 years ago
If attribute A determines both attributes B and C then answers will be:.

A -->B, A-->C.

Rupesh said:   9 years ago
Solution of this question is not right. According to your question an attribute A determines both B and C, then answer must be A->B, A->C or A->(B, C) or A->BC.

Debobrata said:   9 years ago
Apply Decomposition rule on A -> (B, C) we get A -> B and A->C.

Nitish said:   9 years ago
The question is saying that A determines both B and C. But no option suggest that A is determining C.

Really have no idea what should be the correct answer?

Please suggest the correct answer with reason.

Vahini said:   10 years ago
I think answer is correct. By splitting A -> (B, C) to A ->B, A ->C.